2019
DOI: 10.1007/s10098-018-01663-z
|View full text |Cite
|
Sign up to set email alerts
|

Economic value and environmental impact analysis of lignocellulosic ethanol production: assessment of different pretreatment processes

Abstract: Second generation bioethanol represents an interesting alternative for liquid fuels in times of increased concerns over global warming and energy security. However, the recalcitrant structure of lignocellulosic biomass feedstock, makes necessary a pretreatment process to increase the conversion of sugars. Diluted acid (DA), Liquid hot water (LHW), Steam explosion (SE), Ammonia fiber explosion (AFEX) and Organosolv (OS) pretreatment are assessed using a combined economic value and environmental impact (EVEI) an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
32
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 73 publications
(35 citation statements)
references
References 56 publications
3
32
0
Order By: Relevance
“…The environmental assessment was carried out using the simplified approach based on the equivalent CO 2 emissions of the plant [ 43 ].…”
Section: Methodsmentioning
confidence: 99%
“…The environmental assessment was carried out using the simplified approach based on the equivalent CO 2 emissions of the plant [ 43 ].…”
Section: Methodsmentioning
confidence: 99%
“…For example, in 2019 Da Silva et al published an assessment of different LCF pretreatment processes for bioethanol production. Taking into account five different pretreatment procedures of lignocellulosic biomass, the authors found that diluted acid is the best choice for bioethanol production, with an economic value of $39.2 million per year and an environmental impact of 83.9 kt CO 2 per year [62]. Patel et al tried to quantify the production cost of biodiesel from agricultural waste, a comparative assessment recently reported [63].…”
Section: Reported Techno-economic Analysis Studiesmentioning
confidence: 99%
“…Biomass that does not compete directly with the food industry should be used, like agricultural and forest residues [2]. Several works aim to assess a techno-economic analysis of biorefineries producing liquid fuels (i.e., ethanol) [3], solid fuels (i.e., pellet) [5], chemicals (i.e., levulinic acid, succinic acid) [6]. Other works aim to assess supply chain optimization [7] for the biomass-biorefineries.…”
Section: Introductionmentioning
confidence: 99%